2021
DOI: 10.5209/rced.73819
|View full text |Cite
|
Sign up to set email alerts
|

Las competencias emocionales del alumnado de los Grados de Maestro/a en Educación Infantil y Primaria: una dimensión esencial en la formación inicial docente

Abstract: Los cambios producidos durante las últimas décadas, en el contexto social y educativo, hacen fundamental que los/as docentes posean un adecuado nivel de competencias emocionales, para que puedan dar respuesta a las incertidumbres y demandas educativas que en su profesión se les plantean. Por ello, en el presente trabajo se ha pretendido conocer el nivel de competencia emocional autopercibida por 227 estudiantes de primer curso, de los Grados de Maestro/a en Educación Infantil y en Educación Primaria en la Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
3
0
2
Order By: Relevance
“…On the one hand, when considering the participants' degree programs, our results indicated that the undergraduate students in Early Childhood Education claimed a greater knowledge of EI than did their peers pursuing a double degree in Early Childhood and Primary Education. By contrast, García-Vila et al [39] reported that undergraduate students in Early Childhood Education perceived themselves as having lower emotional competencies than did students under a Primary Education degree. As for the year of study, the data indicate that first-year students obtained the highest means, except in the case of general EI knowledge, where the fourth-year students obtained a slightly higher score.…”
Section: Discussionmentioning
confidence: 92%
“…On the one hand, when considering the participants' degree programs, our results indicated that the undergraduate students in Early Childhood Education claimed a greater knowledge of EI than did their peers pursuing a double degree in Early Childhood and Primary Education. By contrast, García-Vila et al [39] reported that undergraduate students in Early Childhood Education perceived themselves as having lower emotional competencies than did students under a Primary Education degree. As for the year of study, the data indicate that first-year students obtained the highest means, except in the case of general EI knowledge, where the fourth-year students obtained a slightly higher score.…”
Section: Discussionmentioning
confidence: 92%
“…The professional exercise of guidance in secondary school presents certain vicissitudes that foster the need for a solid training load linked to the management of one's own emotions and those of others (Prieto, 2018). Some researchers (García-Domingo, 2021;García-Vila et al, 2022) regret the explicit exclusion of emotional competences in initial training programs, since they are essential for the successful development of any activity related to the human being. High school guidance professionals appreciate that, beyond knowledge in specific areas, it is essential to have robust attitudinal training to promote good professional work in the field of educational guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Varios autores (García Domingo, 2021;García Vila et al, 2022;Llorent, 2020;Pérez Escoda et al, 2010;Ruiz Melero et al, 2023) ya han destacado el papel de las emociones en . La identificación de las emociones por parte del profesorado en formación.…”
Section: Objetivosunclassified